ANTHROPOMETRIC CHARACTERISTICS AND BODY FAT MASS IN ELITE BASKETBALL PLAYERS - Dea Karaba Jakovljević; Damir Damir Lukač (Exercise and Quality of Life)
The present study was designed to evaluate the anthropometric parameters, body compositionand anaerobic power components of elite male and female basketball players and comparethem in relation to gender and specific sport demands. The study group consisted of 43 elitenational level athletes: 22 male basketball players (aged 20.3±2.92) and 21 female players(aged 19.5±2.96). The significant differences were noted in fat body mass, triceps and lowerbody region skinfolds, wigh higher values in females, while higher values of forearm, upperarm and waist circumference were noted in males. Comparing Wingate test parameters,higher values of absolute anaerobic power, explosive power, and absolute anaerobic capacitywere recorded in male players, while there was no significant difference in relative anaerobicpower, and relative anaerobic capacity values between genders. Morphometric profile in elitesport should accompany physiological profile in order to monitor improvements duringtraining process and sport performance.